2022
DOI: 10.1007/s12187-022-09940-6
|View full text |Cite
|
Sign up to set email alerts
|

Being a (Female) Child in Baku: Social Order and Understandings of Well-Being

Abstract: What does it mean to be a (female) child in the city of Baku, Azerbaijan? How can we critically interpret the girls’ understandings of well-being considering different forms of compliance with unequal social orders? What conclusions may be drawn from understandings of well- being about the nature of welfare state structures and there-in children’s specific positioning? To answer this question, we conducted qualitative interviews with 13 girls during their various leisure activities. The study shows that parent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…Previous studies on Azerbaijani children's role in traditional (i.e. heteronormative) family environments have also shown that children rarely question their parents' parenting strategies and generally agree with the expectations and demands set for them (Hunner-Kreisel, Nasrullayeva et al, 2022). Similar findings were published on other Muslim-majority post-Soviet States such as Kyrgyzstan (B ühler-Niederberger & Schwittek, 2022).…”
Section: Contextualizing Childhood In Azerbaijansupporting
confidence: 72%
See 1 more Smart Citation
“…Previous studies on Azerbaijani children's role in traditional (i.e. heteronormative) family environments have also shown that children rarely question their parents' parenting strategies and generally agree with the expectations and demands set for them (Hunner-Kreisel, Nasrullayeva et al, 2022). Similar findings were published on other Muslim-majority post-Soviet States such as Kyrgyzstan (B ühler-Niederberger & Schwittek, 2022).…”
Section: Contextualizing Childhood In Azerbaijansupporting
confidence: 72%
“…Yet, there is still a significant gap in the literature around the upbringing of children within families, children's voices and their own understanding of subjective well-being. In their pioneering work, Hunner-Kreisel asked about the well-being of children in Azerbaijan and tried to capture this from the children's own perspectives (Hunner-Kreisel et al, 2020;Hunner-Kreisel, Nasrullayeva et al, 2022). They used a concept of a 'spatial well-being' (Fattore et al, 2021), which studies showed to be limited for children in Baku because children are hardly allocated any place in the public infrastructure that they can use with a certain degree of autonomy.…”
Section: Contextualizing Childhood In Azerbaijanmentioning
confidence: 99%